Therapeutic effect of Chelidonium majus hydro-alcoholic extract alone and in combination with oxaliplatin on ovarian cancer cell line - Zahra Hashempour; Mehdi Noraddini; Majid Nejati; Ameneh Jafari; Mahdi Rafiyan; Amirreza Ostadian; Behrang Alani; Hamed Mirzaei (Discover Oncology)
Abstract Ovarian cancer (OC) is the leading cause of tumor-related deaths among gynecologic cancers. Patients diagnosed with advanced stages of OC urgently require effective therapeutic interventions, but current therapies often fail in patients with recurrent platinum-resistant tumors. Previous research has shown the cytotoxic effects of Chelidonium majus (C. majus) extract on tumors. In this study we have investigated the effects of combined and independent effects of oxaliplatin and C. majus extract on ovarian cancer cell proliferation and apoptosis. Using the OVACR3 cell line as an in vitro model, we applied the MTT assay for cell growth assessment and RT-qPCR to measure caspase-3, β-catenin, and ZEB1 expression. The results demonstrated that both oxaliplatin and C. majus extract significantly inhibited cell growth and promoted apoptosis, with enhanced effects observed when used together. The inhibition of ZEB1 and β-catenin suggest their involvement in the observed anti-cancer effects. Treated groups also showed higher caspase-3 expression compared to controls. Our findings confirm the synergistic potential of combining oxaliplatin and C. majus extract in treating OC, possibly through the ZEB1/β-catenin pathway. Further research is needed to confirm the clinical applicability and underlying mechanisms of this treatment strategy.